РОЗРОБКА КОМПЛЕКСУ ДЛЯ ОБРОБКИ ВОДИ ІМПУЛЬСНИМ БАР’ЄРНИМ РОЗРЯДОМ - Божко , І.В.; Карлов, О.М.; Кондратенко, І.П.; Чарний, Д.В. (Інститут електродинаміки НАН України, Київ, 2017)
Complex for direct processing of contaminated water with pulse dielectric barrier discharge is researched. It consists from a pulse generator and a discharge chamber. The generator is built on the principles of magnetic pulse compression and using of inductive energy storage device, which is switching with the diode with a small time interrupting reverse current (≈40 ns). The generator provides short (~ 100 ns) high-voltage (up to 30 kV) pulses with the energy up to 0.3 J. Pulses acted on the surface of the water, which flowed a thin film (≈0.15 mm) on the surface of the inner electrode of coaxial chamber. In order to obtain the maximum efficiency of water treatment investigated ways of harmonizing the work of all units of the complex. The analysis of the energy loss in transmission from an external source to the load let to conclud that the basic parts of them are linking with the pulse transformer and end section generator connected with chamber. They are requiring careful coordination with other links generator and electrical parameters of the chamber. A processing an aqueous solution methylene blue with an initial concentration of 50 mg/l showed energy yield pulse dielectric barrier discharge at 50% due to impurities up to 75 g/kWh, and for complex as a whole – 22 g/kWh. Referenses. 10, figures 9.